Evaluasi Kepuasan Pengguna Pada Aplikasi Digital Identitas Adminduk (Adinda) Di Desa Tanah Merah Menggunakan Metode Service Quality (Servqual) - Ratna Dewi; Abdullah; Fitri Yunita (Jurnal Pustaka Data (Pusat Akses Kajian Database, Analisa Teknologi, dan Arsitektur Komputer), 2026)
Advances in information technology have prompted the government to improve the quality of digital-based public services, including civil registration services through the digital identitas adminduk (adinda) application in tanah merah village. However, several challenges have been identified in its implementation, such as service delays, data errors, and suboptimal service quality, necessitating an evaluation of user satisfaction with the application. This study aims to determine the level of user satisfaction with the adinda application using the service quality (servqual) method. This study employs a quantitative method with a descriptive approach. Research data were collected through the distribution of questionnaires to 100 respondents who are users of the adinda application in tanah merah village. Data analysis was conducted using validity tests, reliability tests, servqual gap analysis, t-tests, f-tests, and cartesian diagrams. The results indicate that the tangibles and reliability dimensions significantly influence user satisfaction with the adinda application. Meanwhile, the responsiveness, assurance, and empathy dimensions do not significantly influence user satisfaction. The servqual analysis results indicate that the assurance and empathy dimensions have negative gap values, indicating that service quality improvements are still needed, particularly regarding system security and attention to user needs. Additionally, the cartesian diagram results show that several service attributes remain top priorities for improvement to enhance the quality of digital-based civil registration services in tanah merah village.